2012
DOI: 10.1007/s11469-012-9400-7
|View full text |Cite
|
Sign up to set email alerts
|

Aboriginal Gambling and Problem Gambling: A Review

Abstract: The prevention of gambling-related problems amongst Aboriginal communities has been neglected by most public health strategies which concentrate on mainstream populations. Research indicates that rates of problem gambling are higher for Aboriginal groups than the general population. Specific cultural, familial, and social patterns influence gambling by Aboriginal groups, which are individually different, making it difficult to implement a cohesive strategy to address gambling-related harms. Because of this com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 62 publications
(123 reference statements)
1
19
0
Order By: Relevance
“…This result is nonetheless consistent with (Anctil & Chevalier, 2008;Wardman et al, 2001), or slightly higher (Gill, 2010) than the rates observed in other studies conducted among Indigenous Peoples in Canada. It is also comparable to the high rates found in other countries among Indigenous Peoples (see Breen & Gainsbury, 2013).…”
Section: Variablesupporting
confidence: 88%
See 1 more Smart Citation
“…This result is nonetheless consistent with (Anctil & Chevalier, 2008;Wardman et al, 2001), or slightly higher (Gill, 2010) than the rates observed in other studies conducted among Indigenous Peoples in Canada. It is also comparable to the high rates found in other countries among Indigenous Peoples (see Breen & Gainsbury, 2013).…”
Section: Variablesupporting
confidence: 88%
“…The impact of these traumas across generations and their interaction with current stressors may result in problematic outcomes among Indigenous Peoples (Brave Heart & De Bruyn, 1998;Fast & CollinVézina, 2010). Considering the high prevalence of gambling (Breen & Gainsbury, 2013;Williams, Stevens, & Nixon, 2011) and CSA (Collin-Vézina, Dion, & Trocmé, 2009) among Indigenous Peoples, and given that many of these abuses are related to residential schooling (First Nations Information Governance Committee [FNIGC], RHS Regional Coordinators [RCs] & Regional Longitudinal Health Survey [RHS] Team, 2007), further studies are needed to better understand the link between gambling, CSA, and residential schooling. To date, no study has quantitatively investigated the link between residential schools, sexual abuse and gambling among Indigenous persons.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this can relate to Reith and Dobbie's (2011) finding that for some of their predominantly Caucasian sample of UK gamblers, an important early gambling experience was the pro-social uses of winnings and subsequent positive recognition that came with gambling success. Similarly, Breen and Gainsbury (2013) observed that some Native American gamblers associate gambling success with honour and prestige However, caution is required when interpreting the present participants' reported motivations for gambling. It may be that few of those willing to speak of their experiences were willing to report non-communal uses of their gambling winnings, or that those more prone to using winnings on themselves were less likely to volunteer for this study.…”
Section: Discussionmentioning
confidence: 50%
“…Generally, problem behaviours such as substance abuse and gambling are often associated with ethnic minority groups (Nemoto et al, 1999). In a manner reminiscent of Pacific people, minorities elsewhere such as Native Americans and African Americans (Alegria et al, 2009) and Asian-Pacific Islanders (Fong et al, 2010) in the United States, Spaniards in Australia (GAMECS Project, 1999) and Aboriginals in Australia (Breen & Gainsbury, 2013) suffer from higher rates of problem gambling compared to other ethnicities. Māori (indigenous New Zealanders) in New Zealand show similar patterns (Abbott & Volberg, 2000;Abbott et al, 2014;Clarke et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…There have also been studies concluding that minority groups have higher rates of problem gambling (Breen and Gainsbury 2013). People with hearing loss can be considered a minority group, with some even having sign language as their first language (Barnett et al 2011).…”
Section: Introductionmentioning
confidence: 99%